The Effect of Promotion and Consumer Trust on the Decision to Purchase Airline Tickets Online Through Traveloka - Inayah Inayah; Arif Fakhrudin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The development of tourism is increasing rapidly making it easier to spread information about tourism. The people are also interested in visiting and need planes as a means of transportation because it is safe, fast and efficient. As a result, there is an increase in demand for airline tickets. Traveloka is an online ticket booking service provider company which was founded in 2012. This study aims to find out whether there is an influence of promotion and consumer trust on the decision to purchase airplane tickets online through Traveloka. This research method uses a quantitative approach. The number of samples in this study were 100 respondents. The respondents in this study were passengers at Jenderal Ahmad Yani International Airport in Semarang who had bought plane tickets through Traveloka. The sampling technique in this study used the Non-Probability Sampling technique with a purposive sampling approach, which is a sampling technique based on certain criteria who will be used as a sample. Data collection techniques by giving questionnaires to respondents. In analyzing the required validity and reliability tests, multiple linear regression test, t test (partial), f test (simultaneous) and the coefficient of determination. The test results show that the promotion variable (X1) and consumer trust (X2) simultaneously have a positive and significant effect on the decision to purchase (Y) airplane tickets online through Traveloka. The results obtained from the f test were 0.000 0.05, thus proving that H03 was rejected and Ha3 was accepted. Partially the promotion variable (X1) has a positive and significant effect on purchasing decisions (Y) for airplane tickets online through Traveloka. The results obtained from the t test are 0.000 0.05, so H01 is rejected and Ha1 is accepted, while the consumer trust variable (X2) has a partial effect on the decision to purchase (Y) airplane tickets online through Traveloka. The results obtained from the t test were 0.000 0.05, so H02 was rejected and Ha2 was accepted.